2023
DOI: 10.1186/s12888-023-04542-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and related risks of cyberbullying and its effects on adolescent

Abstract: Background Cyberbullying is becoming common in inflicting harm on others, especially among adolescents. This study aims to assess the prevalence of cyberbullying, determine the risk factors, and assess the association between cyberbullying and the psychological status of adolescents facing this problem in the Jazan region, Saudi Arabia. Methods A cross-sectional study was conducted on 355 students, aged between 12–18 years, through a validated onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…The term "cyberbullying" encompasses the deliberate utilization of electronic platforms such as social media, messaging systems, and phone calls to inflict harm on individuals [3]. Online violence encompasses a wide range of manifestations, such as the transmission of hostile, impolite, or derogatory comments, the dissemination of frightening, malicious, and possibly deceptive content to others, the disclosure of sensitive or confidential information (often referred to as exposure), and the act of barring someone from online spaces [4]. This article investigates the underlying factors that contribute to individuals engaging in the transmission of angry, impolite, or offensive communications, specifically focusing on the manifestation of online aggression.…”
Section: What Is Cyberbullying?mentioning
confidence: 99%
“…The term "cyberbullying" encompasses the deliberate utilization of electronic platforms such as social media, messaging systems, and phone calls to inflict harm on individuals [3]. Online violence encompasses a wide range of manifestations, such as the transmission of hostile, impolite, or derogatory comments, the dissemination of frightening, malicious, and possibly deceptive content to others, the disclosure of sensitive or confidential information (often referred to as exposure), and the act of barring someone from online spaces [4]. This article investigates the underlying factors that contribute to individuals engaging in the transmission of angry, impolite, or offensive communications, specifically focusing on the manifestation of online aggression.…”
Section: What Is Cyberbullying?mentioning
confidence: 99%
“…It reached more than 60% in some studies (Kowalski, 2015;Chun, 2020). In Saudia Arabia, a study among 355 students revealed that 42.8% of them were cyberbullied (Gohal, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…With the surge of information and data-sharing platforms, greater digital socialisation and the popularisation of social media, cyberbullying has become more common than ever. It often occurs when there is little adult oversight 7. A nationwide study conducted in the United States of America (USA) reported that at least 37.0% of adolescents aged 12–17 years encountered some form of cyberbullying, including harsh remarks and hurtful comments, rumours and physical threats 8.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, a research by the United Nations Children’s Fund (UNICEF) found that 19.7% of college students were engaged in cyberbullying at least once in their lifetime, while 54.4% of them reported experiencing it at least once 9. Unlike traditional bullying, it is more difficult to identify victims and perpetrators of cyberbullying and to mitigate at homes and schools 7. Furthermore, the rising prevalence of cyberbullying has resulted in adverse impacts on adolescents’ physical and mental health and led to poor academic performances globally 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation